The Legal Consequences Of Serial Marriage For Wives And Children Are Reviewed From The Constitutional Court Decision Number 46/PUU-VIII/2010 And The Compilation Of Islamic Law On The Civil Of Children Against Fathers In Serial Marriages - Nagib, Atikah (Universitas Islam Malang, 2023)
Abstract : Children are gifts from God Almighty that must be maintained and protected because in children are attached dignity, dignity, and rights as human beings. For a child born from a valid marriage has a clear legal position so that obligations and rights arise between parents and children whereas, based on Article 43 of Law No. 1 of 1974 stipulates that